Eficacy Red Ginger in Reduce The Risk of Covid-19 Severity in COPD Patients: A Review - Lorensia, Amelia (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Chronic obstructive pulmonary disease (COPD) is a major global health problem and has an impact on increasing healthcare costs and decreasing productivity. Patients with COPD have a higher prevalence of coronary ischemia and other factors that put them at higher risk for COVID-19-related complications. A strong immune system can help increase the body's resistance so as to reduce the risk in the midst of the COVID-19 pandemic. The use of natural therapy in the treatment of chronic diseases is an opportunity for Indonesia as a tropical country that has many variations of plants that have the potential to become herbal medicines. Red ginger (Zingiber officinale var. rubrum) is one of the most widely consumed medicinal plants in Indonesia. Red ginger has greater anti-inflammatory and antioxidant content than other types of ginger. The antioxidant and anti-inflammatory effects of red ginger in addition to helping reduce the effects of reducing the risk of COVID-19 severity, can also help improve lung function. The preparation of red ginger that has been used in the community is steeping. Therefore, red ginger has the potential to effectively reduce the risk of COVID-19 severity in COPD patients with anti-inflammatory and antioxidant effects in reducing NF-B and the effectiveness of improving lung function.